Assessing Awareness Levels of a Public Health Scheme in India : An Empirical Study - Prakash, N. S.; Chakraborty, Suman; Digal, Sabat Kumar (Prabandhan: Indian Journal of Management, 2023)
Purpose : The ultimate success of any public healthcare scheme mainly depends upon the awareness level among the beneficiaries concerning scheme features and means to access the same. This study aimed to assess the knowledge and comprehension of beneficiaries of Pradhan Mantri Jan Arogya Yojana. Methodology : To examine the level of awareness among the beneficiaries in the state of Karnataka, primary data were collected through a structured questionnaire on a 5-point Likert scale. A sample of 405 beneficiaries was selected among people covered under the Ayushman Bharat scheme between January – December 2021, using a snowball sampling method to check the awareness level of the scheme’s features. Factor analysis was applied to group the 11 factors and measure the percentage of variation explained in the level of awareness of the scheme. The analysis of the data obtained was done by applying ordinal logistic regression. Findings : The study’s findings showed that beneficiaries had a thorough comprehension of the main components of the plan, indicating that awareness levels are significantly positive. Further scope persists for improvement in the government’s mission to be fully achieved in reaching all poor people in time and protecting them from possible adverse financial impacts. Practical Implications : The study findings will help policymakers evaluate the effectiveness of these awareness campaigns, providing valuable insights for further development and refinement of the scheme. Originality : The current research examined the awareness, issues, and their impact on the success of public healthcare schemes through new dimensions.